RETRACTED: Crystal structure and magnetic properties ferrites Ba-Fe-O, Bi-Fe-O, synthesized in NGO “Physics-Sun” - Payzullaxanov Muxammade Sultanxan; Salomov Uktam; Kuchkarov Akmal; Mamatov Olmosbek; Xolmatov Abdurashid (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001